The Needs for Participatory Administration in Educational Institutions Based on Sustainable Development Concepts under the Chiang Rai Primary Educational Service Area Office 3 - Sittisan, Apilat; Meprom, Kasidit (An Online Journal of Education, 2025)
This research aimed to study the need for participatory administration in educational institutions based on sustainable development concepts. The sample consisted of 322 school administrators and teachers under the Chiang Rai Primary Educational Service Area Office 3, selected through simple random sampling. A questionnaire was used as the research instrument. A questionnaire was used as the research instrument. Statistics used for data analysis included percentage, mean, standard deviation, and modified priority needs index (PNIModified). The research findings revealed that the highest priority needs were decision-making (PNIModified = 0.344), followed by goal-setting (PNIModified = 0.342), benefit-sharing (PNIModified = 0.340), operations (PNIModified = 0.332), and trust (PNIModified = 0.331) respectively.